Opioids for cancer‐related pain in children and adolescents - Wiffen, Philip J (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the analgesic efficacy, and adverse events, of opioids used to treat cancer pain in children and adolescents between birth and 17 years, in any setting.